Memanfaatkan Aplikasi Pinterest Sebagai Referensi Untuk Membuat Konten Digital Marketing - Fajar Ariwibowo, Muhammad; Swadaya Hidayat, Intra; Putri Andita, Mirza; Mawarindani Indra, Azalia (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
Digital transformation has become an urgency for all business sectors. One of the changes related to the business sector is the marketing pattern switching to digital, or what is called digital marketing. SMKN 3 Sekayu, South Sumatra, only has an engineering major. SMKN 3 hopes that their teachers will be able to create digital marketing content that helps market products or services or for their own career or business needs through the SMK Industry 4.0 Digital Marketing Teacher Workshop. The method used in this community service is to use educational methods for the community as well as advocacy and training, and the application used is the Pinterest application. The results of this dedication produce additional knowledge for the audience to create content and increase the number of ideas for creating digital marketing content. Apart from that, 93.06% were very satisfied with the workshops they had attended.